Makna Serambeak pada Etnik Rejang di Kabupaten Rejang Lebong - Sandera, Rizki; Canrhas, Amril; Sarwono, Sarwit (UNIB Press, 2025)
This study aims to determine the meaning of Serambeak in baséun bekulo performed by the Rejang ethnic group. The research method used is ethnographic qualitative research method. The data for this study were obtained through a field study which included the text of Serambeak and audio-visual recordings of Serambeak during the Baséun Bekulo event. Sources of data from this research are observation, documentation, interviews with informants who are considered to have knowledge and understanding of serambeak as well as direct observation. The research location is in Kesambe Baru Village, East Curup District, Rejang Lebong Regency. Data analysis techniques were carried out using the stages of transcript, translation, interpretation and meaning. After conducting the analysis, the results of this study are the meaning of serambeak which belongs to the Rejang ethnic community. Starting from the meaning of the word Serambeak comes from the word Rambeak which means chat, discussion or words that are in accordance with the Rejang language or baso ejang. Serambeak in the Rejang language dictionary means a proverb; like; the saying of the Rejang people. Baséun Bekulo is an activity of negotiating or interacting between two parties, usually carrying out this event where there is deliberation for consensus in the application process in the stages leading to their marriage, all the words from the beginning to the end of the event are called serambeak. The essence of serambeak is to find an agreement on the taste and convey the results of the taste. Serambeak describes the life of the Rejang people, one of which is politeness, respect, demonstrating power, advice, and expressions of proverbs. In addition, serambeak also has an important function in society as a function of education, projection or imagination, and cultural institutions.